Eficiencia en el uso de bases de datos digitales para la producción científica en universidades de Colombia (2016)
This paper presents an assessment of efficiency in the use of digital databases (DD) for scientific production in Colombian accredited universities in 2013. The methodology used was the Data Envelopment Analysis (DEA). The number of DD and the number of tenured professors were used as input. The number of scientific publications indexed in Scopus was used as output. The results show an inefficient use of inputs to produce scientific publications at most of the universities analyzed. The policy recommendations are: the joint purchase of DD, the use of open access resources, and to adjust policies of incentives for research by international trends.